Pengaruh Variabel Makroekonomi dan Rasio Profitabilitas Terhadap Harga Saham di Sektor Industri Barang Konsumsi Pada Indeks Saham Syariah Indonesia (ISSI) Periode 2018 – 2022 - -, Cupian - (Jurnal Ilmiah Ekonomi Islam, 2024)
This study emphasizes the analysis of the effect of Macroeconomic variables (Gross Domestic Product and Inflation), Profitability Ratios (Return on Assets, Return on Equity and Gross Profit Margin) and the COVID - 19 period on stock prices in the consumer goods industry sector on the Indonesian sharia stock index. Determination of the sample in this study using purposive sampling based on the research period, namely 2018 - 2022 and the type of data is secondary, while the analysis method used is multiple linear regression models with panel data. The results of this study indicate that the Gross Domestic Product, Inflation, Return on Assets and Gross Profit Margin variables have a positive and significant effect, the Return on Equity variable has a negative and insignificant effect and the covid period variable as a dummy variable has a negative and significant effect on stock prices in the consumer goods industry sector on the Indonesian sharia stock index (ISSI) 2018 - 2022.